Attributes of Foreign Subsidiaries and the Location Strategy of Multinational Firms in Global Cities in Latin America. Issue 3 (2nd October 2017) - Izumi, Paulo Kazuhiro; Burnier, Pedro Carvalho; Ogasavara, Mário Henrique; de Figueiredo, Júlio César Bastos
ABSTRACT: International business research has recently honed in on the subnational dimension of multinational enterprises (MNEs), particularly the city level. Through a binomial logistic regression of data from 254 foreign subsidiaries of 10 Latin American global cities between 2006 and 2012, we found that specific attributes of the firm related to the industrial sector, subsidiary control, and ownership level have a positive effect on the location choice in cities. In addition, we found that in the previous period and during the international financial crisis, MNEs exploited their internalization advantages more intensely by exerting greater control over their subsidiaries in global cities.